2016
DOI: 10.1155/2016/2712476
|View full text |Cite
|
Sign up to set email alerts
|

A Green Antioxidant Activity‐Integrated Dual‐Standard Method for Rapid Evaluation of the Quality of Traditional Chinese Medicine Xuebijing Injection by On‐Line DPPH‐CE‐DAD

Abstract: Much attention has been focused on treatment of sepsis which leads to high mortality all over the world in every year. Antioxidant activity seems to play a prominent role in the treatment of sepsis exhibited by Xuebijing injection. The aim of the present research was to develop an on-line 1, 1-diphenyl-2-picrylhydrazyl- (DPPH-) capillary electrophoresis-diode array detector (on-line DPPH-CE-DAD) method for rapidly assessing antioxidant properties and efficacious material basis of antioxidant activity as a way … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Our analysis predicted TNF, IL-6, IFNγ, and IL-1β are among the top 10 important nodes in the aGVHD molecular network (genecards.com). Network pharmacology analysis and literature search revealed that 38 compounds detected in XBJ ingredients may benefit patients receiving allo-HSCT therapy and those suffering from aGVHD, including active compounds in XBJ that were detected in serum such as paeoniflorin and carthamin yellow (Huang et al, 2011; Li et al, 2016a; Zuo et al, 2017a,b). Our analysis suggested XBJ may prevent aGVHD at different phases.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis predicted TNF, IL-6, IFNγ, and IL-1β are among the top 10 important nodes in the aGVHD molecular network (genecards.com). Network pharmacology analysis and literature search revealed that 38 compounds detected in XBJ ingredients may benefit patients receiving allo-HSCT therapy and those suffering from aGVHD, including active compounds in XBJ that were detected in serum such as paeoniflorin and carthamin yellow (Huang et al, 2011; Li et al, 2016a; Zuo et al, 2017a,b). Our analysis suggested XBJ may prevent aGVHD at different phases.…”
Section: Discussionmentioning
confidence: 99%
“…These factors were the main ones influencing investigation. In several papers on study of antioxidant activity using CE and DPPH published before 24 26 , the optimized parameters were similar to the ones described here. Hence, the parameters chose to explore for the optimum performance were comprehensive and necessary.…”
Section: Resultsmentioning
confidence: 99%
“…The capillary electrophoresis (CE) has the advantages of low solvent consumption and high efficiency, so it was widely applied in screening enzyme inhibitors, complex samples analysis, and derivatization [18,19,20] in recent years. At present, the in-capillary ABTS + -CE-DAD method [21] and DPPH-CE-DAD method [22,23] were established to evaluate the antioxidant activity of TCM. Based on these methods, an in-capillary [Fe(ferrozine) 3 ] 2+ -CE-DAD was proposed to evaluate the ferrous ions chelating ability of TCM.…”
Section: Introductionmentioning
confidence: 99%